The Study of the Various VLSI Design Method (International Journal of Innovative Research in Computer Science & Technology, 2022)
VLSI outlooks for the Very Large Scale  Integrated, and this is a very advanced electronic  technology. VLSI circuits have been used in a variety of  applications, including microcontrollers, microcomputers,  n chips, chips used in a graphics processor, camcorders, and video cameras. The notion of the "VLSI design  approach" is discussed in this article, and research  methodologies for VLSI design are provided using flow  charts. The results of VLSI design, as well as the status of  the methodologies and numerous infrastructures and  designs associated with the VLSI design programme and  approach, were also illustrated in this article. A network  security branch, silicon implementation systems, a  semiconductors section, and semiconductor foundries  from throughout the world are all part of the VLSI  architecture design. Since it is responsible for  manufacturing processes and development such as  transistor count, processing shrinkage, voltages scaling,  timers gating, and fuzzy logic control, this research  examines the newest growth and advances of low power  VLSI. VLSI power loss is a well-known problem,  according to the research, because this limited VLSI is in  charge of the manufacturing implementation, including  transistor size, process shrinkage, voltage scaling, clock  gating, and so on. This study also aims to demonstrate and  illustrate current and future trends in low-power VLSI  research and innovation. In the realm of electronics, VLSI  has a wide variety of applications.
Keywords: Dynamic Power; Leakage power; Very Large - Scale Integrated (VLSI); VLSI design